Numerical simulation of thermal distribution and residual stress characteristic for laser wobble joining of CFRTP and Ti-6Al-4V alloy. (July 2022) - Bu, Hengchang; Zhan, Xiaohong; Yang, Hongyan; Wang, Feiyun; Ma, Wanping
Abstract: The joining of light alloy and carbon fiber reinforced thermoplastics composite (CFRTP) is recently considered to be an effective way to meet the lightweight requirements of components manufacturing in the aviation field. Furthermore, laser joining technology presents an innovative method for joining CFRTP and light alloy with the advantage of high precision, high efficiency and non-contact. In this paper, a thermo-mechanically coupled model for laser wobble joining of CFRTP and Ti-6Al-4V alloy has been established with the combined heat source, which has not been comprehensively studied in the published research. The typical features of the temperature field and the distribution characteristic of the residual stress are analyzed thoroughly under various parameters, whereas the optimized process parameters are attained in terms of the size of the resin melting zone (RMZ) at the interface as well as the maximum value of residual stress. In addition, a validation experiment was implemented to substantiate the established model. The results indicate that the size of RMZ at the interface enlarges appreciably with higher laser power and lower scanning speed. The distinct residual stress concentration around the weld and the asymmetric residual stress concentration inside the CFRTP can be principally interpreted with the comprehensive effect of non-uniform heat input and fixture constraints during the laser joining process. Moreover, according to the size of RMZ as well as the maximum value of residual stress, the optimum parameters are eventually determined as scanning speed of 0.015 m/s and laser power of 2000 W. The simulated result presents substantial consistency with the verification experimental result, therefore corroborating the validity and accuracy of the established model. Highlights: The thermo-mechanically coupled model for laser wobble joining of CFRTP and Ti-6Al-4V alloy is established with the combined heat source, while the validity and accuracy of the established model are substantiated with the verification experiment. The evolution of the temperature field and the distribution characteristic of residual stress for the laser wobble joining of CFRTP and Ti-6Al-4V alloy are analyzed comprehensively. The effect of process parameters is further explored on the melting behavior of resin at the joint interface and the distribution characteristic of residual stress. The process parameters are optimized according to the size of the resin melting zone at the interface and the maximum value of residual stress.